Shadow economy analyses : case of Russia - Novitskaia, Marina; Slaný, Martin, 1982-; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
As the share of the shadow economy in Russia is one of the highest, it has a great impact on country’s socio-economic indicators. Understanding the scope of the shadow economy is crucial for the development of the state. In addition, the establishment of causal relationships is an important aspect for the development of further measures to deal with the illegal economy. Various academic studies have proved that the higher the unemployment rate, the bigger the size of the shadow economy. The thesis explores the hypothesis on the example of the economic situation in Russia to answer the question whether this assumption holds to the particular country. It investigates the following hypothesis: the unemployment rate is positively correlated with the shadow economy in Russia. In the theoretical part mainly the definition, causes, methods of estimation of the shadow economy, global trends are represented on the basis of the literature reviewed. In addition, there is an analysis of the shadow economy in Russia, in particular, its structure and development pattern.In the practical part the size of the Russian underground economy is estimated, as well as the relationship between the size of the shadow economy and the level of unemployment are investigated using the MIMIC model. The MIMIC approach considers the statistical theory of latent variables, which examines several causes and several indicators of the shadow economy. The size of the shadow economy is applied as a “latent” variable. This thesis contributes a lot to the studying of the shadow economy in Russia as there are not many published researches that investigate the relationship between the shadow economy and the unemployment rate. The empirical part proves the hypotheses that the shadow economy is positively correlated with the unemployment rate in Russia. Thus, some unemployed workers earn money on the underground market. However, this relationship is weak.
The mean value of the shadow economy in Russia for the period 1999-2018 is 38,373 % of GDP.
Vedoucí práce: Martin Slaný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses